Pendugaan Umur Simpan Cookies Jagung Menggunakan Pendekatan Kadar Air Kritis - Sugiyono, Sugiyono IPB (Perum BULOG, 2016)
The critical moisture of corn cookies was 0,0674 gH2O/g solid. The sorption isotherm of corn cookies was evaluated using six equation models i.e. Hasley, Chen-Clayton, Henderson, Caurie, Oswin and Guggenheim-Anderson-de Boer (GAB). The best equation model to describe corn cookies sorption isotherm phenomenon was GAB. Calculation results showed that the shelf life of corn cookies packed in metalized polyethylene and stored at 85 percent relative humidity was 298 days.